Methylene blue at recommended concentrations alters metabolism in early zebrafish development - Niepukolie Nipu; Lai Wei; Lauren Hamilton; Hyojin Lee; Jith Thomas; Jan A. Mennigen (Communications Biology)
Abstract Methylene blue (MB) is an antifungal agent widely used during critical stages of zebrafish development. Most guidelines recommend 0.00005% or 0.0001% of MB for embryo/larval rearing. The Organisation for Economic Co-operation and Development zebrafish embryo toxicity test guideline omits MB recommendations, leading to inconsistent MB use in zebrafish research. Because MB affects oxidative energy metabolism in vitro and in vivo, we investigate possible metabolic effects of recommended MB concentrations in developing zebrafish (1–5 days post-fertilization (dpf)). MB increases O2 consumption rate at 1 dpf, followed by an overall reduction in oxidative energy metabolism in post-hatch eleutheroembryos (4–5 dpf). Concomitantly, mitochondrial transcripts decrease in 1 and 4 dpf zebrafish. Our findings show that MB, at recommended husbandry concentrations, affects oxidative metabolism and can thus confound experiments. Since the zebrafish embryo/larval model is gaining traction as a high-throughput New Approach Methodology (NAM) for toxicity assessment, researchers should reconsider MB use.